IMPLEMENTASI KEBIJAKAN IZIN PROSEDUR BARU BPOM TENTANG CARA PENGAJUAN NOTIFIKASI KOSMETIKA - Tri Widyastuti, Ambar; Rahmawati, Rita; Rusliandy, Rusliandy (Administratie: Jurnal Administrasi Publik, 2022)
The study aims to determine how the implementation of the BPOM Licensing Policycosmetic notifications. This study uses a qualitative descriptive analysis approach, which s a method that functions to describe or provide an overview of the object under study through interviews as a measuring tool from the sample that has been collected as t s, without analyzing and making generally accepted conclusions. The interview method used s an n-Depth interview and this interview s carried out with BPOM employees who are authorized n the Licensing Procedure. The implementation of BPOM's New Procedure Permit policy on How to Submit Cosmetic Notifications makes t easier for business actors or producers to register their products to be marketed by means of registration that s easy, safe, and convenient. With the many assistances provided by BPOM such as socialization of new regulations or policies virtually, the virtual registration of notifications also makes t much easier for producers. The BPOM s ready to help with the presence of competent human resources who can direct producers n overcome the obstacles faced n filing cosmetic notifications.